Social Facilitation: A Review and Alternative Conceptual Model - Ferris, Gerald R.; Beehr, Terry A.; Gilmore, Davìd C. (Academy of Management Review, 1978)
Previous research literature is reviewed in light of certain weaknesses and inadequacies of drive theory explanation, indicating a need for a more cognitive approach. A more cognitive model, constructed in an expectancy theory framework, is presented as a plausible alternative explanation for possible effects of social facilitation on employees. Recommendations are made regarding directions of future research for testing the model.